2019
DOI: 10.1080/03055698.2019.1584852
|View full text |Cite
|
Sign up to set email alerts
|

Peer integration, teacher-student relationships and the associations with depressive symptoms in secondary school students with and without special needs

Abstract: View related articles View Crossmark data Citing articles: 1 View citing articles Peer integration, teacher-student relationships and the associations with depressive symptoms in secondary school students with and without special needs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 31 publications
(26 reference statements)
1
13
0
Order By: Relevance
“…Previous research mostly reported poorer relationships between SEN students and their teachers (Murray and Greenberg, 2001;Al-Yagon and Mikulincer, 2004;Murray et al, 2006;Freire et al, 2020) and fewer opportunities to participate at school than TD students (Coster et al, 2013). Our results show the opposite, as Schwab and Rossmann (2020) similarly showed in a recent study that found SEN students rated their teacher-student relationships more positively than TD students.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Previous research mostly reported poorer relationships between SEN students and their teachers (Murray and Greenberg, 2001;Al-Yagon and Mikulincer, 2004;Murray et al, 2006;Freire et al, 2020) and fewer opportunities to participate at school than TD students (Coster et al, 2013). Our results show the opposite, as Schwab and Rossmann (2020) similarly showed in a recent study that found SEN students rated their teacher-student relationships more positively than TD students.…”
Section: Discussionsupporting
confidence: 61%
“…O'Donnell and Reschly (2020) state that the inconsistence in school connectedness or teacher-student relationships in the literature on SEN students could be attributable to the availability of resource rooms and close relationships with special education teachers in each context. Similarly, Schwab and Rossmann (2020) explain their results by arguing that in the Austrian school system, SEN students are often supported by two teachers in regular classrooms, one of whom is a special needs teacher who spends much time with the students, providing opportunities to develop a closer relationship with them. We think the same hypothesis could explain our positive results for teacher-student relationships and the better perception of participation of the SEN students in our sample, as such students attending public mainstream schools in Chile receive academic support by special needs teachers in regular classrooms and additional support in small groups in a special resource room.…”
Section: Discussionmentioning
confidence: 96%
“…The teacher is not only a manager of social relations in class, but also an attachment figure who has an important role in the students' development process (Schwab & Rossmann, 2020). Research on the role of the student-teacher relationship (STR) has been inspired by extended attachment theory (Bowlby, 1982;Hamre & Pianta, 2001), based on the idea that warm relationships between children and teachers might promote emotional security in students (Sabol & Pianta, 2012).…”
Section: The Student-teacher Relationshipmentioning
confidence: 99%
“…Previous studies showed that, in general, children with Special Educational Needs (SEN) tend to have a poorer student-teacher relationship than their peers (Prino et al, 2016). Also, negative student-teacher relationships seem to be associated with more depressive symptoms in children with SEN (Schwab & Rossmann, 2020).…”
Section: Student-teacher Relationships In Children With Special Educational Needsmentioning
confidence: 99%
“…Previous studies have indicated that experiences of social exclusion can produce negative effects on students' self-esteem (Harris, Qualter, and Robinson 2013). Students who feel isolated describe greater anxiety, frustration and sadness during their stay in school (Nelson et al 2016) and run a higher risk of developing depressive symptoms (Schwab and Rossmann 2020).…”
Section: Introductionmentioning
confidence: 99%